A Newborn with Congenital Hyperinsulinism. (3rd September 2019) - Du, Yiting; Ju, Rong; Xi, Yufeng; Gou, Peng
Abstract: Objective: Our aim was to describe the molecular alterations in the ABCC8 gene in a child with congenital hyperinsulinism (CHI).Methods: Genetic analysis of the ABCC8 gene of a newborn infant with congenial hyperinsulinism was obtained.Results: There were two mutations in the ABCC8 gene, c.4412delT, and c.3979G > A, indicating a compound heterozygous mutation. The c.4412delT variant is associated with CHI, and the c.3979G > A variant is associated with neonatal diabetes. Treatment with diazoxide was not effective, octreotide treatment with acetate was effective.Conclusion: The combination of a mutation of the ABCC8 gene c.4412delT, associated with CHI, and the mutation of c.3979G > A, associated with neonatal diabetes, resulted in a neonate with hypoglycemia. The mechanism remains unclear.